A case report of McCune–Albright syndrome with hepatic manifestations - Mohammad Haddadi; Elahe Lal Kheirkhah; Mojgan Ansari; Samieh Ahmadzade; Zeinab Taraz; Saeid Yazdi (Clinical Case Reports, 2022)
Abstract McCune–Albright syndrome is a non‐hereditary disease characterized by café‐au‐lait skin spots, fibrous dysplasia of bone, and endocrinopathies. We report a boy with a history of repeated hospitalizations from birth due to severe jaundice and hyperthyroidism. At the age of 2 years, he suffered from a proximal left femoral fracture. During the follow‐up, liver function tests were abnormal. Considering the clinical and paraclinical findings, the patient was diagnosed with McCune–Albright syndrome.